A novel approach to sharing all available information from funded health research: the NIHR Journals Library - David Wright; Elaine Williams; Colin Bryce; Andrée le May; Ken Stein; Ruairidh Milne; Tom Walley (BMC, 2018)
Abstract Background Relevant information on health research must be made publicly available in an accurate, timely and accessible manner if evidence is to inform practice and benefit patient care. Failure to publish research information represents a significant waste of research funds. However, recent studies have demonstrated that non-publication and selective or biased reporting remains a significant problem. The role of online publications in rectifying these issues by providing open access to study information is increasingly recognised. Objective This paper details a novel approach to publishing research information developed by the National Institute for Health Research (NIHR), a major funder of health research in the United Kingdom. The NIHR has enhanced its Journals Library (www.journalslibrary.nihr.ac.uk), providing an online repository of information from research funded through five programmes. We describe how the NIHR Journals Library provides a 'thread' of relevant information for each study, including protocols, participant information sheets, data linkages, final reports, publications and diverse knowledge products. We also discuss the Library as a 'living' resource, one that is updated as each study progresses from inception to completion. Finally, we consider the implications of the Library for the NIHR, other journals and research teams submitting information. Conclusion Openly publishing information from funded research in the NIHR Journals Library serves as a model of knowledge sharing, maximising return on investment and enhancing the usability and replicability of research findings for different evidence-user communities. The Library also supports wider 'research on research' ambitions, enabling users to interrogate the repository of NIHR-funded studies, enhancing the understanding of research commissioning, design, dissemination and impact. Video abstract: www.youtube.com/watch?v=8H03uxN_iTE.